'Your DNA, Your Say': global survey gathering attitudes toward genomics: design, delivery and methods - Middleton, Anna; Niemiec, Emilia; Prainsack, Barbara; Bobe, Jason; Farley, Lauren; Steed, Claire; Smith, James; Bevan, Paul; Bonhomme, Natasha; Kleiderman, Erika; Thorogood, Adrian; Schickhardt, Christoph; et al. (Personalized medicine, 2018)
Our international study, 'Your DNA, Your Say', uses film and an online cross-sectional survey to gather public attitudes toward the donation, access and sharing of DNA information. We describe the methodological approach used to create an engaging and bespoke survey, suitable for translation into many different languages. We address some of the particular challenges in designing a survey on the subject of genomics. In order to understand the significance of a genomic result, researchers and clinicians alike use external databases containing DNA and medical information from thousands of people. We ask how publics would like their 'anonymous' data to be used (or not to be used) and whether they are concerned by the potential risks of reidentification; the results will be used to inform policy.
Gesehen am 15.04.2020